Healing Memories : Puerto Rican Women's Literature in the United States - García, Elizabeth (Writer on Puerto Rican women's literature) (Book collections on Project MUSE., 2018)
"Using an interdisciplinary approach, Healing Memories analyzes the ways that Puerto Rican women authors use their literary works to challenge historical methodologies that have silenced the historical experiences of Puerto Rican women in the United States. Following Aurora Levins Morales's alternative historical methodology she calls 'curandera history, ' this work analyzes the literary work of authors, including Aurora Levins Morales, Nicholasa Mohr, Esmeralda Santiago, and Judith Ortiz Cofer, and the ways they create medicinal histories that not only document the experiences of migrant women but also heal the trauma of their erasure from mainstream national history. Each analytical chapter focuses on the various methods used by each author including using the literary space as an archive, reclaiming memory, and (re)writing cultural history, all through a feminist lens that centers the voices and experiences of Puerto Rican women"--